2023
DOI: 10.1017/s0954579423001037
|View full text |Cite
|
Sign up to set email alerts
|

Critical examination of resilience and resistance in African American families: Adaptive capacities to navigate toxic oppressive upstream waters

Velma McBride Murry,
Juliet M. Nyanamba,
Rachel Hanebutt
et al.

Abstract: African American families navigate not only everyday stressors and adversities but also unique sociocultural stressors (e.g., “toxic upstream waters” like oppression). These adverse conditions are consequences of the historical vestiges of slavery and Jim Crow laws, often manifested as inequities in wealth, housing, wages, employment, access to healthcare, and quality education. Despite these challenges, African American families have developed resilience using strength-based adaptive coping strategies, to som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 153 publications
0
2
0
Order By: Relevance
“…Although media reports have shared that Black/African Americans are reporting disproportionate challenges and disruptions to their psychosocial health due to being impacted by the "double pandemic", this study identified Black/African American respondents as having lower levels of psychological distress than other groups [32,[38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 71%
“…Although media reports have shared that Black/African Americans are reporting disproportionate challenges and disruptions to their psychosocial health due to being impacted by the "double pandemic", this study identified Black/African American respondents as having lower levels of psychological distress than other groups [32,[38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 71%
“…Research on the neurobiology of resilience blossomed when the tools for reliable assessments of processes within the human body became more feasible, including assessments of stress biology, gene methylation, immune function, and brain function (Feder et al, 2019;Feldman, 2021;Gunnar, 2020;Masten & Cicchetti, 2016;McEwen, 2020;McLaughlin et al, 2020;Shonkoff et al, 2021). Research focused on sociocultural processes, acculturation, discrimination, social justice, and historical trauma gained more attention (e.g., Jones et al, 2023;Marks et al, 2020;Murry et al, 2023;Panter-Brick, 2023;Spencer, 2023;Motti-Stefanidi, 2023;Suárez-Orozco et al, 2018;Wilbur & Gone, 2023). Multisystem measures of protective factors became prominent, such as the Child and Youth Resilience Measure (Ungar & Liebenberg, 2011) and indices of positive (rather than adverse) childhood experiences, such as the Benevolent Childhood Experiences scale (Narayan et al, 2023).…”
Section: Shared Assumptions and Concepts Of Dp And Drsmentioning
confidence: 99%